Modeling the relationship between 231Pa/230Th distribution in North Atlantic sediment and Atlantic meridional overturning circulation - Siddall, Mark; Stocker, Thomas F.; Henderson, Gideon M.; Joos, Fortunat; Frank, Martin; Edwards, Neil R.; Ritz, Stefan P.; Muller, Simon A. (Paleoceanography, 2007)
[1] Down-core variations in North Atlantic Pa-231(xs)/Th-230(xs) have been interpreted as changes in the strength of the Atlantic meridional overturning circulation (AMOC). This modeling study confirms that hypothetical changes in the AMOC would indeed be recorded as changes in the distribution of sedimentary Pa-231(xs)/Th-230(xs). At different sites in the North Atlantic the changes in sedimentary Pa-231/ Th-230 that we simulate are diverse and do not reflect a simple tendency for (231)Paxs/Th-230(xs) to increase toward the production ratio (0.093) when the AMOC strength reduces but instead are moderated by the particle flux. In its collapsed or reduced state the AMOC does not remove Pa-231 from the North Atlantic: Instead, Pa-231 is scavenged to the North Atlantic sediment in areas of high particle flux. In this way the North Atlantic Pa-231(xs)/Th-230(xs) during AMOC shutdown follows the same pattern as Pa-231(xs)/ Th-230(xs) in modern ocean basins with reduced rates of meridional overturning (i.e., Pacific or Indian oceans). We suggest that mapping the spatial distribution of Pa-231(xs)/Th-230(xs) across several key points in the North Atlantic is an achievable and practical qualitative indicator of the AMOC strength in the short term. Our results indicate that additional North Atlantic sites where down-core observations of Pa-231(xs)/Th-230(xs) would be useful coincide with locations which were maxima in the vertical particle flux during these periods. Reliable estimates of the North Atlantic mean Pa-231(xs)/Th-230(xs) should remain a goal in the longer term. Our results hint at a possible "seesaw-like'' behavior in Pa-231/Th-230 in the South Atlantic.